2018
DOI: 10.1021/acs.jmedchem.7b01515
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Morpholino-2H-pyrido[3,2-b][1,4]oxazin-3(4H)-ones as Nonsteroidal Mineralocorticoid Antagonists

Abstract: A novel series of morpholine-based nonsteroidal mineralocorticoid receptor antagonists is reported. Starting from a pyrrolidine HTS hit 9 that possessed modest potency but excellect selectivity versus related nuclear hormone receptors, a series of libraries led to identification of morpholine lead 10. After further optimization, cis disubstituted morpholine 22 was discovered, which showed a 45-fold boost in binding affinity and corresponding functional potency compared to 13. While 22 had high clearance in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In the search for a nonsteroidal antagonist to avoid limitations associated with steroidal agents, Pfizer proceeded with library screening that led to the identification of morpholine hit 120 (Figure ) . After further optimization efforts, and using the morpholine scaffold for variable substitution (at positions 2, 4, and 5), a potent MR antagonist with oral bioavailability (compound 121 , Figure ) was developed.…”
Section: Pharmacological Activity Of Morpholine Derivatives On Varioumentioning
confidence: 99%
“…In the search for a nonsteroidal antagonist to avoid limitations associated with steroidal agents, Pfizer proceeded with library screening that led to the identification of morpholine hit 120 (Figure ) . After further optimization efforts, and using the morpholine scaffold for variable substitution (at positions 2, 4, and 5), a potent MR antagonist with oral bioavailability (compound 121 , Figure ) was developed.…”
Section: Pharmacological Activity Of Morpholine Derivatives On Varioumentioning
confidence: 99%
“…This extended hydrogen-bonding network is important both for ligand recognition and for the positioning of helix 12 (not shown) in the active receptor conformation . Recently, Piotrowski et al also reported a similar description of the three regions in the ligand-binding pocket of MR . With the three key receptor regions identified, we generated a pharmacophore model and searched the AstraZeneca compound collection for compounds with matching complementary structural features.…”
Section: Resultsmentioning
confidence: 93%
“…For instance, Pfizer found that the installation of a methyl group to a morpholinecontaining compound of mineralocorticoid receptor (MR) agonist, gave rise to a 45-fold potency increase. 10 In the past decade, a large number of LSF approaches have been developed, including metal-catalyzed transformations, 11−21 visible-lightinduced photocatalysis 22−34 and enzyme catalysis, 35−43 among others (Scheme 1a). 44−48 Electrochemical synthesis is a robust tool for sustainable molecular syntheses since it generally features mild reaction conditions, high selectivities, and facile scalability by flow techniques (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of a small group can dramatically affect the bioactivity profiles of a structurally complex pharmaceutical molecule. For instance, Pfizer found that the installation of a methyl group to a morpholine-containing compound of mineralocorticoid receptor (MR) agonist, gave rise to a 45-fold potency increase . In the past decade, a large number of LSF approaches have been developed, including metal-catalyzed transformations, visible-light-induced photocatalysis and enzyme catalysis, among others (Scheme a). …”
Section: Introductionmentioning
confidence: 99%